Recent developments in unmanned aerial vehicle (UAV) surveys for rock slope stability analysis—a review - Muhammad Junaid; M. E. Al-Atroush; Sajid Mahmood; Kausar Sultan Shah; Arshad Ullah (Geocarto International)
The existence of most of the cut and natural slopes in morphological complex areas makes it impossible to characterize the discontinuities along the rock slope using conventional scanline mapping and geological compass. Consequently, the unmanned aerial vehicle (UAV) survey has gotten greater attention from numerous researchers in recent decades. This research presents a detailed review of the UAV surveys and their applicability of precise determination of discontinuity orientations and spacings along the rock slope. As the discontinuities characterization is carried out in rock slope only, therefore the scope of review article is limited to rock masses. The review article is composed of three sections. The first section compares the applicability of various UAV sensors followed by detail explanation of fundamental principles of UAV survey, such as data acquisition, data processing, and extraction. The next section provides a brief introduction and comparison of various types of UAVs platforms. It is followed by review of the applications of UAV photogrammetry for slope stability assessment, such as kinematic analysis, rock mass quality characterization, and slope deformation monitoring based on previous work. The primary aim of this review article is that no review article was published previously that assess the applicability of UAV photogrammetry in characterization of the entire slope on limited number of Rock Quality Designation (RQD) data. In this paper, a real case study is presented to estimate the area of various RQD indices along the slope. Based on the RQD maps, the area of poor, fair, good, and excellent rock were computed as 1382, 3039, 393, and 37 m2. This shows that the UAV can obtain precise discontinuity spacing and is a reliable way of characterizing the rock mass quality. The previous study reveals that UAV photogrammetry is currently an extensively applied approach for performing kinematic analysis, and slope deformation study. However, its application in rock mass quality characterization is not yet fully adopted. Furthermore, the capability of UAV to be equipped with various geophysical equipment, such as gravity, ground penetrating radar (GPR), and electromagnetic instrument forecast it increasing applications in future for geotechnical investigation.